User guide to the sustainable early generation seed business analysis tool (SEGSBAT) - Rajendran, S.; McEwan, M. (International Potato Center, 2021)
The sustainable early generation seed business analysis tool (SEGSBAT) is a Microsoft Excel-based tool to help early generation seed producers to estimate their total production costs, customer seed requirement, and production calendar to determine a budget, and amount of source seed needed, among other functions. The step-by-step excel-platform requires some accounting skills, but it is moderately easy to use, and users can adjust it to fit their own situation. SEGSBAT allows an enterprise to set prices for early generation seed that are low enough to attract customers, but high enough to cover production costs and make the seed business financially sustainable. The tool generates two financial scenarios, one with and one without external funding, so that a company can create a revolving fund that will eventually replace donor support. The tool has been used mainly for sweetpotato, but is being adapted for cassava and other crops. In the future, non-economic functions can be added, e.g. to plan for environmental sustainability.